INKONSISTENSI PENGATURAN KEWENANGAN JAKSA DALAM MELAKUKAN PENINJAUAN KEMBALI PADA UU NO. 11 TAHUN 2021 TENTANG KEJAKSAAN REPUBLIK INDONESIA (STUDI PUTUSAN MK NOMOR 20/PUU-XXI/2023): Juridicial Review of Inconsistencies in The Regulation of The Prosecutor’s Authority to Conduct Judicial Review in Law No. 11 of 2021 Concerning The Prosecutor’s Office of The Republic of Indonesia (Study of Constitutional Court Decision Number 20 / PUU-XXI / 2023) - Revydo Daniel Pranoto; Reni Dwi Purnomowati (Faculty of Law, Universitas Trisakti, 2025)
Prosecutors have the legal authority to request a judicial review under Article 30C letter h of Law Number 11 of 2021, which pertains to the Prosecutor's Office of the Republic of Indonesia. The prosecutor's submission of a judicial review has the capacity to create discord and uncertainty. The author will employ normative juridical research methodology for conducting this thesis research. The data utilized in this research consists of secondary data derived from primary, secondary, or tertiary legal materials. The result research and conclusion, according to Constitutional Court Decision No. 20/PUU-XXI/2023, the authority of the Prosecutor to perform a Judicial Review has been deemed unconstitutional. The decision affirms that the convicted individual or their successors possess the right to judicial review, whereas the prosecution lacks the power to initiate such a review. Under Law No. 11/2021 on the Prosecutor's Office, prosecutors are granted the authority to carry out judicial reviews.